Maternal occupational exposure to polycyclic aromatic hydrocarbons and craniosynostosis among offspring in the national birth defects prevention study. Issue 1 (2nd June 2015) - O'Brien, Jacqueline L.; Langlois, Peter H.; Lawson, Christina C.; Scheuerle, Angela; Rocheleau, Carissa M.; Waters, Martha A.; Symanski, Elaine; Romitti, Paul A.; Agopian, A.J.; Lupo, Philip J.; ,
Abstract : Background: Evidence in animal models and humans suggests that exposure to polycyclic aromatic hydrocarbons (PAHs) may lead to birth defects. To our knowledge, this relationship has not been evaluated for craniosynostosis, a birth defect characterized by the premature closure of sutures in the skull. We conducted a case‐control study to examine associations between maternal occupational exposure to PAHs and craniosynostosis. Methods: We used data from craniosynostosis cases and control infants in the National Birth Defects Prevention Study (NBDPS) with estimated delivery dates from 1997 to 2002. Industrial hygienists reviewed occupational data from the computer‐assisted telephone interview and assigned a yes/no rating of probable occupational PAH exposure for each job from 1 month before conception through delivery. We used logistic regression to assess the association between occupational exposure to PAHs and craniosynostosis. Results: The prevalence of exposure was 5.3% in case mothers (16/300) and 3.7% in control mothers (107/2, 886). We observed a positive association between exposure to PAHs during the 1 month before conception through the third month of pregnancy and craniosynostosis (odds ratio [OR] = 1.75; 95% confidence interval [CI], 1.01–3.05) after adjusting for maternal age and maternal education. The number of cases for each craniosynostosis subtype limited subtype analyses to sagittal craniosynostosis; the odds ratio remained similar (OR = 1.76, 95% CI, 0.82–3.75), but was not significant. Conclusion: Our findings support a moderate association between maternal occupational exposure to PAHs and craniosynostosis. Additional work is needed to better characterize susceptibility and the role PAHs may play on specific craniosynostosis subtypes. Birth Defects Research (Part A) 106:55–60, 2016. © 2015 Wiley Periodicals, Inc.